Integration Entrepreneurial Marketing and Experiential Marketing in Enhance Brand Loyalty on Local Coffee Industry in Gombengsari - Kukuh Judy Handojo; Sudarmiatin Sudarmiatin; Agus Hermawan (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
SMEs in Indonesia currently contribute only 15.7% to national exports, compared to Thailand, where the export has reached 29%. Therefore, there is significant scope for improvement to increase the contribution, ultimately will give a positive impact to the broader economy, given nearly 90% of the human resources are employed in the SME sector, which benefits from a wealth of natural and other resources. The main issues frequently encountered by SMEs are by optimizing available resources and adhering to established standards to ensure products are market-ready and compliant with the regulators. Qualitative approach conducted within SMEs Local Processor to obtain in-depth insight regarding barriers and constraints encountered, along with the challenges that need to be completed with numerous limitations and a lack of government support. Based on the in-depth interview result, the finding indicates that a significant majority of SMEs Local coffee processor practitioners primarily focus on financial resources in order to grow whereas the other that should be optimized and developed, on both individual and group basis, receive in sufficient attention. Therefore, through an understanding of the available strengths and which are not necessarily possessed by competitors, especially from other countries, the product produced by SMEs Local coffee processors should be capable of competing in the global market by understanding VRIO concept in a resource based view or Valuable, Rare, Inimitable, and Organize. Thus numerous products from SMEs will gain recognition by the global market.